Determination of Slope Safety Factor Based on Hoek & Brown Collapse Criteria on Ampera-Surumana Road Section - Nugraha, Agung; Uno, Irianto; Asrafil, Asrafil (Tadulako Science and Technology Journal, 2024)
Introduction: One way to determine whether a slope is stable or not is by using the safety factor criterion. The method to determine the safety factor using the limit equilibrium method. Administratively the research area is located in the village of Salubomba, Central Banawa District, Donggala Regency, Central Sulawesi Province. The results of the study are also expected to be used as one of the basis for planning the design of stable slopes in the area Method: The methods used in this research were qualitative and quantitative. The process in this research was carried out with each method. The process of collecting secondary data and primary data is carried out by Geology and Geological Engineering methods both qualitatively and quantitatively. Results and Discussion: Observations in this study were made in the field in the form of observations of bridging on road slopes. The bruises in the study area are grouped on the basis of their shape and genetics. Through the results of observations and measurements on rock slopes at the research site. Based on data processing on the GEOSTUDIO 2018 R2 software application. Then, the value of the slope safety factor at observation station 1 is 2.316. Conclusion: Based on testing and analysis of the Hoek & Brown collapse criteria method, it can be concluded that the value of the slope safety factor at observation stations 1, 2, 3, 4, and 5 is 2.316; 2.029; 1.765; 1.658; 2.622 respectively. At station 4 the level of vulnerability is medium (Landslides can occur), at station 3 is at a low level of vulnerability (Landslides rarely occur), while at stations 1,2 and 5 are at a very low level of vulnerability (Landslides very rarely occur).